ANALISIS ISI STRUKTUR PERIKLANAN PERTANIAN INDONESIA PADA JARINGAN INTERNET INDONETWORK (CONTENT ANALYSIS OF ADVERTISING STRUCTURE OF INDONESIAN AGRICULTURE ON INTERNET NETWORK OF INDONETWORK) - Supriyanto, Supriyanto; Kusumawardani, Dyah Pertiwi; Subejo, Subejo (Jurnal Ilmu-Ilmu Pertanian, 2006)
The research was purposed to identify agricultural advertising structure in Indonesia on Indonetwork.co.id. Indonetwork has served a lot of agricultural advertising document and good system of archives which it was easy to be accessed. Basic method used in the study was descriptive analysis by using content analysis. Method of sampling was simple random sampling. A number of 800 agricultural advertising items has been selected randomly from 1733 of agricultural advertising items. The selection of sample in each province was done by using proportional frequencies approach. Proportional test and ANOVA test were used in the study in order to identify the trend of agricultural advertising structure in Indonesia at Indonetwork.The research showed that a larger number of agricultural product agency in the western part of Indonesia which have been advertized at Indonetwork was dominant. The persuasive content of advertising materials appeared in a bigger proportion. The cooperative opportunities have appeared on several advertising items explicitly. The Indonesian and combination of Indonesian and English were dominant as advertising language. There were only two companies in western part of Indonesia which got feedback from consumers. The advantages of agricultural advertising structure at Indonetwork may have a good chance to compete on global market widely.